Erhöhte Komorbidität bei Vaskulitis-Patienten (Aktuelle Rheumatologie, 2017)
Englund M et al. Comorbidities in Patients with Antineutrophil Cytoplasmic Antibody-associated Vasculitis versus the General Population.